Royalty Hak Kekayaan Intelektual sebagai Harta Bersama dalam Perkawinan di Indonesia : Trilemma Yuridiksi - Suryahartati, Dwi (Recital Review, 2024)
This research aims to reveal that royalties as intangible movable objects can be counted as assets in marital property. Various perspectives such as Islamic law, civil law, and the Indonesian National Marriage Law fight to strengthen the argument. This research is normative legal research that is prescriptive in nature using a conceptual approach, a statutory approach, and a comparative approach. Empirically, intellectual property rights are difficult to be considered objects that can be shared. The main focus in this research is on the legal and ethical aspects that underlie profit sharing in the context of intellectual property as a right. On the other hand, the civil law perspective explores the secular law that regulates the distribution of royalties. This article examines the issue of managing legal conflicts between several different legal systems and identifies points of convergence and divergence between Islamic legal perspectives and intellectual property law and marriage law.